Work-life balance : experiences of professional working mothers - Dayang Kartini, Abang Ibrahim; Farida, Abdul Halim; Hii, Hiong Ling (2011)
Nowadays, Malaysian women who participate in workplace have increased throughout the year. The increasing numbers of the woman in workplace cause the issue of work life balance as important task around woman in Malaysia. This study explored the experiences of professional working mothers on work life balance among work, family and selves in the context of both public and private sector in Sarawak. The sample included 7 professional working mothers; ranging from 35 to 46 years of age, having at least two children. The researchers used the interview technique for collecting the data. Qualitative semi structured interview were audio-taped. An interview inventory was prepared beforehand and its validity was checked in consultation with the research supervisor and other experts in the university. The study showed that professional working mothers are related to work life balance issues and responsible in performing their domestic and professional roles, besides individual role. The proper integration of both roles will succeed with the stipulation of flexibility from organization. Based on the findings, reasons that lead professional working mothers quit work due to family and work matters. Different ways on balancing the work, family and individual roles is crucial for professional mothers to gain satisfaction with their career. The response rate from the sample was low, fortunately rich and contextual information which was received during interviews, overcome these flaws. Some of the females from the targeted population were somewhat reluctant to give the audio taped interviews. This paper contributes to the earlier research made in this area, study explored what type of hindrance or support a working mother acquired from organization and family and how to integrate both in present circumstances.